A global treatments for coronaviruses including COVID‐19. Issue 12 (11th May 2020) - Yousefi, Bahman; Valizadeh, Saeid; Ghaffari, Hadi; Vahedi, Azadeh; Karbalaei, Mohsen; Eslami, Majid
Abstract: In late December 2019 in Wuhan, China, several patients with viral pneumonia were identified as 2019 novel coronavirus (2019‐nCoV). So far, there are no specific treatments for patients with coronavirus disease‐19 (COVID‐19), and the treatments available today are based on previous experience with similar viruses such as severe acute respiratory syndrome‐related coronavirus (SARS‐CoV), Middle East respiratory syndrome coronavirus (MERS‐CoV), and Influenza virus. In this article, we have tried to reach a therapeutic window of drugs available to patients with COVID‐19. Cathepsin L is required for entry of the 2019‐nCoV virus into the cell as target teicoplanin inhibits virus replication. Angiotensin‐converting‐enzyme 2 (ACE2) in soluble form as a recombinant protein can prevent the spread of coronavirus by restricting binding and entry. In patients with COVID‐19, hydroxychloroquine decreases the inflammatory response and cytokine storm, but overdose causes toxicity and mortality. Neuraminidase inhibitors such as oseltamivir, peramivir, and zanamivir are invalid for 2019‐nCoV and are not recommended for treatment but protease inhibitors such as lopinavir/ritonavir (LPV/r) inhibit the progression of MERS‐CoV disease and can be useful for patients of COVID‐19 and, in combination with Arbidol, has a direct antiviral effect on early replication of SARS‐CoV. Ribavirin reduces hemoglobin concentrations in respiratory patients, and remdesivir improves respiratory symptoms. Use of ribavirin in combination with LPV/r in patients with SARS‐CoV reduces acute respiratory distress syndrome and mortality, which has a significant protective effect with the addition of corticosteroids. Favipiravir increases clinical recovery and reduces respiratory problems and has a stronger antiviral effect than LPV/r. currently, appropriate treatment for patients with COVID‐19 is an ACE2 inhibitor and a clinical problem reducing agent such as favipiravir in addition to hydroxychloroquine and corticosteroids. Abstract : In late December 2019 in Wuhan, China, several patients with viral pneumonia were identified as 2019 novel coronavirus (2019‐nCoV). So far, there are no specific treatments for patients with coronavirus disease‐19 (COVID‐19), and the treatments available today are based on previous experience with similar viruses such as severe acute respiratory syndrome‐related coronavirus (SARS‐CoV), Middle East respiratory syndrome coronavirus (MERS‐CoV), and Influenza virus. In patients with COVID‐19, hydroxychloroquine decreases the inflammatory response and cytokine storm, but overdose causes toxicity and mortality. Neuraminidase inhibitors such as oseltamivir, peramivir, and zanamivir are invalid for 2019‐nCoV and are not recommended for treatment but protease inhibitors such as lopinavir/ritonavir (LPV/r) inhibit the progression of MERS‐CoV disease and can be useful for patients of COVID‐19 and, in combination with Arbidol, has a direct antiviral effect on early replication of SARS‐CoV. Favipiravir increases clinical recovery and reduces respiratory problems and has a stronger antiviral effect than LPV/r. Currently, appropriate treatment for patients with COVID‐19 is an angiotensin‐converting‐enzyme 2 inhibitor and a clinical problem reducing agent such as favipiravir in addition to hydroxychloroquine and corticosteroids.